Prawne aspekty rozwoju wysokotemperaturowych reaktorów jądrowych w Polsce — głos w dyskusji - Nowacki, Tomasz R. (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
High-temperature nuclear reactors are among the technologies that can be used in energy and heating. In particular, these reactors can be used in the industry as a source of high-temperature technological heat, thus eliminating fossil fuels such as coal and gas, and enabling energy-intensive enterprises to produce electricity and heat for their own needs. One of the important factors for the development of this technology is the appropriate legal framework. In 2017, the advisory team of the Minister of Energy published a report on the possibility of implementing high-temperature reactors in Poland. This report, apart from technical and economic aspects, also touched upon legal issues. This text is a voice in the discussion on this subject, partially polemic with the findings of the report, pointing to some erroneous assumptions and proving that the construction of high--temperature reactors in Poland can be carried out on the basis of the currently existing regulations.
Keywords: atomic law; nuclear law; high temperature reactors; licensing of nuclear reactors